전술 무선랜에서의 인증기반 적응적 채널 도약 기법 - Jae Min Jeung (The Graduate School, Ajou University, 2012)
As the military continues its transformation towards network centric warfare (NCW), a quickly-deployable communication solution for a tactical operations center (TOC) is required. The U.S. Army uses secure wireless local area network (SWLAN) with IEEE 802.11 standard waveforms to quickly set up TOC communications without cables. The SWLAN provides extremely secure mobile wireless data communications with COMSEC, TRANSEC, and monitoring systems to encrypt data and detect PHY / MAC layer misbehaviors. In the near future, our military is going to adopt the SWLAN in tactical information communication network (TICN) due to above reasons. However, the SWLAN hardly prevents jamming attacks of MAC / PHY layer. Therefore, adversaries are likely to exploit the vulnerabilities. In this thesis, we show the weakness of the MAC / PHY layer and propose the authentication-based adaptive channel hopping scheme to overcome the weakness. Firstly, we analyze the characteristics of the SWLAN, its environments, and security holes. Secondly, we propose the authentication-based medium access control to mitigate the weakness of the MAC layer. Finally, we introduce the adaptive rapid channel hopping and outband-sensing based channel hopping scheme to overcome the weakness of the PHY layer. Simulation results and theoretical analysis show that the proposed schemes enhance the performance under the jamming environments. We hope that the proposed schemes can be applied practically in SWLAN for improving the operation effectiveness.
학위논문(박사)아주대학교 일반대학원 :NCW학과,2012. 2
Keywords: IEEE 802.11+ anti-jamming